USING OF SINGLE EXPONENTIAL SMOOTHING (SES) METHOD FOR SALES OF GAMIS AT RATNA JAYA SHOP - Azmira, Tiara; Nasution, Akmal; Sumantri, Sumantri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2024)
Abstract: Toko Ratna Jaya is a business in the fashion sector that sells women's robes and is experiencing instability in its sales because Toko Ratna Jaya is unable to predict their sales for the following month. Ratna Jaya Shop currently carries out forecasting only by relying on the owner's predictions. However, this approach is less efficient and can lead to losses or increased stock costs if forecasting is inaccurate. To increase the accuracy of the estimates, the use of the Single Exponential Smoothing Method is proposed. This method smooths past values with exponential weights, placing greater emphasis on recent data. Use of data from the last 1 (one) year as reference data for recording the past for forecasting experiments for the next 1 (one) month. Experiments using different Alphas test accuracy in actual situations. The results of the experiment with an alpha of 0.2 are almost the same as the actual value in predicting the situation one month into the future with the lowest error, namely MAPE 12.05% and forecasting sales of gamis of 1,476 pcs.Keywords: forecasting; gamis; sales; single exponential smoothing (SES); toko ratna jaya. Abstrak: Toko Ratna Jaya adalah usaha di bidang fashion yang menjual baju gamis wanita dan sedang mengalami ketidakstabilan dalam penjualannya dikarenakan Toko Ratna Jaya tidak mampu meramalkan penjualan mereka untuk bulan berikutnya. Toko Ratna Jaya saat ini melakukan peramalan hanya dengan mengandalkan paraduga pemiliknya. Namun, pendekatan ini kurang efisien dan dapat menyebabkan kerugian atau peningkatan biaya stok jika peramalan tidak akurat. Untuk meningkatkan ketepatan perkiraan, penggunaan Metode Single Exponential Smoothing diusulkan. Metode ini menghaluskan nilai masa lalu dengan bobot eksponensial, memberikan penekanan lebih besar pada data terbaru. Penggunaan data 1 (satu) tahun terakhir sebagai data acuan pencatatan masa lalu untuk percobaan peramalan untuk 1 (satu) bulan kedepan. Eksperimen menggunakan Alpha yang berbeda menguji akurasi dalam situasi aktual. Hasil dari eksperimen dengan alpha 0,2 hampir sama dengan nilai aktual dalam meramalkan keadaan satu bulan ke depan dengan error yang paling rendah yaitu MAPE 12,05% dan peramalan penjualan gamis sebanyak 1.476 pcs.Kata kunci: gamis; penjualan; peramalan; single exponential smoothing (ses); toko ratna jaya.